How do elementary school teachers shape their students' self-regulated and creativity in learning mathematics? - Bistari, Bistari; Hamdani, Hamdani; Rustam, Rustam; Dashela, Tarina; Mumtazah, Nadia Wardah; Veven, Veven (Institute of Advanced Engineering and Science, 2024)
So far, mathematics learning has only focused on a curriculum that prioritizes outcomes over processes, so attitudes are rarely the target of learning. In fact, a positive attitude, especially self-regulated and creativity, is needed in learning mathematics and must have been formed since elementary school. This research, with the aim of describing efforts to establish independence and creativity in learning mathematics by elementary school teachers in West Kalimantan, uses a qualitative descriptive method with a questionnaire as a research instrument. The results of the study show that: (i) the formation of self-regulated learning by the teacher is very good, especially in the indicators of disciplined behavior. However, it needs to be improved on indicators of behaving based on one's own initiative; and (ii) the formation of learning creativity by the teacher is very good, especially on the indicator of having a great curiosity. However, it needs to be improved on indicators of diligent behavior and not getting bored easily.